2022
DOI: 10.1186/s12864-022-08338-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide localization of histone variants in Toxoplasma gondii implicates variant exchange in stage-specific gene expression

Abstract: Background Toxoplasma gondii is a protozoan parasite that differentiates from acute tachyzoite stages to latent bradyzoite forms in response to environmental cues that modify the epigenome. We studied the distribution of the histone variants CenH3, H3.3, H2A.X, H2A.Z and H2B.Z, by genome-wide chromatin immunoprecipitation to understand the role of variant histones in developmental transitions of T. gondii parasites. Results H3.3 and H2A.X were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 77 publications
2
13
1
Order By: Relevance
“…After defining the STs, we analyzed their chromatin architecture. Our detailed analysis of H2A.X, H3.3, and H3K9me3 enrichment throughout the subtelomeric region supports the heterochromatic composition of STs, as previously observed [ 31 ]. H3K9me3 is a recognized mark of repeat-rich constitutive heterochromatin [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…After defining the STs, we analyzed their chromatin architecture. Our detailed analysis of H2A.X, H3.3, and H3K9me3 enrichment throughout the subtelomeric region supports the heterochromatic composition of STs, as previously observed [ 31 ]. H3K9me3 is a recognized mark of repeat-rich constitutive heterochromatin [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…Histone marks and variants were analyzed in every chromosome. The global histone analysis showed clear peaks for H3K9me3, H3.3, and H2A.X at regions delimiting the ends of the chromosomes [ 31 ]. A detailed analysis of ChIP-seq assays ( Table S2 ) showed that the intensities and/or peaks of these histones decreased from the chromosome end toward the centromere in most cases, being more evident for H3.3 and H2A.X ( Figure 2 A and Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations